Shaping the digital enterprise : trends and use cases in digital innovation and transformation - Oswald, Gerhard; Kleinemeier, Michael (Springer, 2017)
"This book sheds light on cross-industry and industry-specific trends in today's digital economy. Prepared by a group of international researchers, experts and practitioners under the auspices of SAP's Digital Thought Leadership & Enablement team within SAP's Business Transformation Services (BTS) unit, the book furthermore presents relevant use cases in digital transformation and innovation. The book argues that breakthrough technologies have matured and hit scale together, enabling five defining trends: hyper-connectivity, supercomputing, cloud computing, a smarter world, and cyber security. It presents in detail how companies are now reimagining their products and services, business models and processes, showcasing how every business today is a digital business. Digitalization, defined as the process of moving to a digital business, is no longer a choice but an imperative for all businesses across all industries and regions. Taking a step toward becoming a digital enterprise is demanding and challenging. The dimensions of customer centricity, leadership and strategy, business models, including offerings (products and services), processes, structure and governance, people and skills, culture, and technology foundation can serve as orientation for digitalization. The articles in this book touch on all dimensions of this digital innovation and transformation framework and offer possible answers to some of the pressing questions that arise when practitioners seek to digitalize their business"--Provided by publisher.
Keywords: Information technology -- Management.; Business enterprises -- Technological innovations.; Business -- Data processing.; Electronic commerce.; Management information systems.; elektronické knihy; electronic books